Isomerization and fragmentation of polyatomic molecules induced by ultraviolet and extreme UV light - Pathak, Shashank (Kansas State University, 2021)
Imaging molecular structures evolving at their natural timescales, during a chemical reaction, with an atomic-scale resolution has been a long-standing goal for physicists and chemists. With the recent developments in experimental techniques, as well as the light sources, such as synchrotron radiation sources, free-electron lasers (FELs), ultrafast lasers, and high-harmonic sources, it is now possible to study the molecular dynamics and structural changes with femtosecond (in some cases attosecond) time-resolution, for near-infrared to x-ray wavelengths. These advancements are particularly useful in studying a wide range of photoinduced chemical reactions and photoinduced fragmentation. In this thesis, some of the advanced techniques are used to study photoinduced isomerization and fragmentation. This thesis also partly focuses on developing the tools and techniques which can be used to study these molecular structural changes. Several molecular systems are studied throughout the thesis. Some of them are studied with the goal of understanding the chemistry post photoexcitation and photo-fragmentation, while others were aiming for method development for future experiments. Specifically, some of the experiments are performed on a prototypical heterocyclic ring molecule, thiophenone. One such experiment studies photochemistry after ultraviolet light absorption, using time-resolved photoelectron spectroscopy at a free-electron laser. The experimental results are combined with ab-initio molecular dynamics and electronic structure calculation for the ground state and excited state molecules, which revealed insights about the electronic and nuclear dynamics. Ring-opening is the most dominant process upon photoexcitation, driven by a ballistic extension of C-S bond, and is completed within ~350 fs. The ground state trajectories also confirm the formation of three ring-opened products, providing detailed insights into this reaction. Ring-opening reactions of similar types are considered as candidates for designing fast molecular switches. In another study, the fragmentation pathways of thiophenone are studied using ion-electron coincidence experiments. With these experiments, it is observed that some of the fragmentation pathways may be decoupled purely based upon the photoelectron energy, which is also a measure of the internal energy of an ion. Another method, which is often used to study dissociation, fragmentation, and isomerization pathways, is coincident ion momentum imaging. The sensitivity of this method in distinguishing similar-looking structures is demonstrated by distinguishing conformational isomers of 1,2-dibromoethane, which only differ by a rotation around a single bond and coexist in a particular ratio at any given temperature. Sequential and concerted breakup pathways were disentangled using a newly developed Native frames method to obtain information about the initial molecular geometry. These experiments may trigger future time-resolved studies to monitor subtle molecular structural changes using coincidence ion momentum imaging. The work presented in this thesis uses a wide variety of techniques to understand light-induced isomerization and fragmentation dynamics, from simple molecules to moderately complex systems. This work contributes to the understanding developed for the prototypical systems, which may help formulate general principles underlying some light-induced reactions and processes.
Keywords: Photoionization; Light-induced processes; Photophysics